Biolubricants feedstocks, catalysts, and nanotechnology - Singh, Yashvir; Singh, Nishant Kumar; Sharma, Abhishek (Green tribology and tribochemistry, 2024)
Due to their biodegradability, renewability and superior lubrication performance compared to commercial fossil lubricants, vegetable oils are becoming substitutes for petroleum-based lubricants in different sectors, especially in the automotive industry. Biolubricants covers feedstocks, physicochemical properties, process to chemically alter raw oils from feedstocks, lubrication characteristics, as well as the additives to enhance properties